Respiratory Syncytial Virus–related Community Chronic Obstructive Pulmonary Disease Exacerbations and Novel Diagnostics: A Binational Prospective Cohort Study - Wiseman, Dexter J.; Thwaites, Ryan S.; Ritchie, Andrew I.; Finney, Lydia; Macleod, Mairi; Kamal, Faisal; Shahbakhti, Hassan; van Smoorenburg, Lisa H.; Kerstjens, Hiub A. M.; Wildenbeest, Joanne; Öner, Deniz; Aerssens, Jeroen; et al. (American journal of respiratory and critical care medicine, 2024)
Respiratory syncytial virus (RSV) is a common global respiratory virus that is increasingly recognized as a major pathogen in frail older adults and as a cause of chronic obstructive pulmonary disease (COPD) exacerbations. There is no single test for RSV in adults that has acceptable diagnostic accuracy. Trials of RSV vaccines have recently shown excellent safety and efficacy against RSV in older adults; defining the frequency of RSV-related community infections and COPD exacerbations is important for vaccine deployment decisions. This prospective study aimed to establish the frequency of outpatient-managed RSV-related exacerbations of COPD in two well-characterized patient cohorts using a combination of diagnostic methods. Participants were recruited at specialist clinics in London, United Kingdom, and Groningen, the Netherlands, beginning in 2017 and observed for three consecutive RSV seasons, during exacerbations, and at least twice yearly. RSV infections were detected by RT-PCR and serologic testing. A total of 377 patients with COPD attended 1,999 clinic visits and reported 310 exacerbations. There were 27 RSV-related exacerbations (8.7% of the total); of these, seven were detected only by PCR, 16 only by serology, and four by both methods. Increases in RSV-specific Nucleoprotein antibody were as sensitive as those in the antibody to Pre-Fusion or Post-Fusion for serodiagnosis of RSV-related exacerbations. RSV is associated with 8.7% of outpatient-managed COPD exacerbations in this study. Antibodies to RSV Nucleoprotein may have diagnostic value and are potentially important in a vaccinated population. The introduction of vaccines that prevent RSV is expected to benefit patients with COPD.